2012
DOI: 10.1080/07448481.2011.584335
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Stalking Among College Students: The Disparity Between Researcher- and Self-identified Victimization

Abstract: Stalking is a serious problem in the college community. A concern that needs to be addressed is the disparity between the number of those who met the behavioral criteria for stalking victimization, but who did not self-identify as a victim. The consequences of stalking victimization are highlighted. Recommendations for addressing this issue on campus are detailed in a plan that may help improve the retention, progression, and graduation rates for stalking victims.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
14

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 23 publications
0
20
0
14
Order By: Relevance
“…In fact, all four sex dyads were taken equally seriously by a range of professional and non professional groups. It is worth noting here that if one or more dyads are far less likely to self-identify as a stalking vicim, then they wouldn't have completed the study questionnaire (although McNamara and Marsil's 2012 findings would argue against this notion).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In fact, all four sex dyads were taken equally seriously by a range of professional and non professional groups. It is worth noting here that if one or more dyads are far less likely to self-identify as a stalking vicim, then they wouldn't have completed the study questionnaire (although McNamara and Marsil's 2012 findings would argue against this notion).…”
Section: Discussionmentioning
confidence: 96%
“…In McNamara and Marsil's (2012) examination of the disparity between researcherand college Same and opposite sex stalking student-identified victim status, 26% of women and 22% of men self-identified as stalking victims.…”
Section: Opposite Sex Stalkingmentioning
confidence: 99%
“…Furthermore, according to the recently published Campus Climate Survey on Sexual Assault and Sexual Misconduct administered at the University of Pennsylvania, 3.1% of undergraduates reported that they had been stalked while attending the university (Cantor et al, 2015). Numerous studies of college student populations report similarly high rates of stalking victimization (e.g., Belknap & Sharma, 2014; Buhi, Clayton, & Surrency, 2009; McNamara & Marsil, 2012).…”
Section: Stalking Victimizationmentioning
confidence: 99%
“…Victims of stalking often do not identify themselves as such (see McNamara & Marsil, 2012). Given that 43% of the college student participants in the McNamara and Marsil's study were identified as stalking victims according to indirect behavioral indicators, 75% failed to identify themselves as victims.…”
Section: Stalkingmentioning
confidence: 99%
“…This attention is also deservedly pointed at college students, given that 74% stalking victims range in age between 18 and 39 years (McNamara & Marsil, 2012). Jordan, Wilcox, and Pritchard (2007) report that 13% to 27% college women bear the brunt of stalking behavior.…”
Section: Stalkingmentioning
confidence: 99%